Green Economy as a Strategy for Developing Tourism Villages: An Islamic Ethical and Values Approach to Sustainable Tourism - Suprianik Suprianik; Avinda Avinda; Zainuri Zainuri (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to analyze the application of the principleGreen Economy in the strategy for developing tourist villages, reviewed from an ethical approach and Islamic values ​​of sustainable tourism. This study aims to determine the application of the principles of sustainable tourism. Green Economy In the strategy of developing tourist villages and to determine how the ethical approach and Islamic values ​​in sustainable tourism. This study adopted a qualitative method with a case study research type. The research location is in Kampung Durian, which is located in Pakis Village, Panti District, Jember Regency. Data collection techniques used include observation, interviews, and documentation. The validity of the data used in this study is ensured by source triangulation. The results of this study indicate that, 1) Kampung Durian Panti Jember Tourism Village has implemented the principlesGreen Economy in the development of tourist villages, although its implementation is still not fully optimal. 2) The ethical approach and Islamic values ​​in sustainable tourism basically require the management of tourism villages to pay attention to the principle of balance between the economy and the environment, which places tourism activities as part of the human mandate in maintaining the sustainability of nature (caliph on earth), ensuring social welfare, and avoiding environmental damage (facade). In Islamic economic studies, this principle is in line withgreen economywhich emphasizes resource efficiency, ecological sustainability, and social justice.